The Effect of Fermented Rice Straw with Eco Enzyme on Percentage Non Carcas of Local Sheep - Hasnudi; L. K. Pardosi; Yunilas (Jurnal Peternakan Integratif, 2021)
Most sheep are kept in the countryside as it is easy to maintain and have high economic value. This study aims to determine the effect of feeding fermented rice straw combine with odot grass (Pennisetum purpureum cv ) on the percentage of non-carcass ofÂ  local sheep. Rice straw was fermented by eco enzyme. The research method used was a completely randomized design experiment (CRD) with five treatments and four replications while the treatments were given as P0 = 0% fermented rice straw, P1 = 25% fermented rice straw, P2 = 50% fermented rice straw, P3 = 75% fermented rice straw and P4= 100% fermented rice straw. Parameters observed were head weight percentage without skin, leg weight percentage without skin, skin weight percentage, tail weight percentage without skin, trachea and lungs weight percentage, liver weight percentage, heart weight percentage, blood weight percentage, intestine weight percentage, compound belly weight percentage. The results showed that the administration of 25% fermented rice straw combine with odot grass caused better non-carcass percentage, such as the percentage of skin, the percentage of the head without skin, the percentage of the leg without skin, the percentage of liver, the percentage of the heart, the percentage of the trachea and lungs, the percentage of the stomach compound and blood percentage. Based on the results of the study, it is known that the use of 25% fermented rice straw combine with odot grass on male local sheep give the best result on non-carcass and can be an alternative feed for sheep.